2002
DOI: 10.1590/s0041-87812002000300006
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism following struma ovarii tumor resection: a case report

Abstract: Struma ovarii is an infrequent ovarian tumor, and there are only few reports with detailed data of thyroid function. In several cases, malignant struma ovarii have been shown to produce hyperthyroidism, but there is no reported case of hypothyroidism following struma ovarii tumor resection. A 62-year-old white woman underwent right ovary resection that had a pathologic diagnosis of struma ovarii. After 6 days, she developed weakness, myalgia, somnolence, nausea, and arterial hypotension. Laboratory tests showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 8 publications
3
10
0
1
Order By: Relevance
“…Thyroid tissue is the predominant element of a struma ovarii, and varying clinical features of hyperthyroidism are present in 7% of patients, whereas 25–33% will have abnormal thyroid function tests without any symptoms (11) . Clinical hypothyroidism following resection of a benign struma ovarii has also been reported (18) . In our case, the thyroid function tests obtained on the third postoperative day revealed a mild hypothyroidism with slightly decreased free thyroxine and increased TSH levels.…”
Section: Discussionsupporting
confidence: 67%
“…Thyroid tissue is the predominant element of a struma ovarii, and varying clinical features of hyperthyroidism are present in 7% of patients, whereas 25–33% will have abnormal thyroid function tests without any symptoms (11) . Clinical hypothyroidism following resection of a benign struma ovarii has also been reported (18) . In our case, the thyroid function tests obtained on the third postoperative day revealed a mild hypothyroidism with slightly decreased free thyroxine and increased TSH levels.…”
Section: Discussionsupporting
confidence: 67%
“…In 5% to 12% of cases, functional thyroid tissue may be present in struma ovarii; and classic symptoms of hyperthyroidism may be evident [2][3][4]8,16]. The functional thyroid tissue in the ovary may represent the patient's only functional thyroid tissue, and hypothyroidism may occur after resection [17,18]. It has been reported that struma ovarii normally do not exceed a diameter of 10 cm [19].…”
Section: Discussionmentioning
confidence: 99%
“…Multicystic ovaries with hypothyroidism have been reported in prepubertal girls [1][2][3][4][5], but very few cases in adult females have been published [4,6]. The present report involves the case of an adult female with primary hypothyroidism with ovarian cysts.…”
Section: Introductionmentioning
confidence: 92%